2010
DOI: 10.1038/nn.2646
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 induces and maintains neural stem cells

Abstract: Neural stem cells (NSCs) are uncommitted cells of the CNS defined by their multipotentiality and ability to self renew. We found these cells to not be present in substantial numbers in the CNS until after embryonic day (E) 10.5 in mouse and E5 in chick. This coincides with the induction of SOX9 in neural cells. Gain- and loss-of-function studies indicated that SOX9 was essential for multipotent NSC formation. Moreover, Sonic Hedgehog was able to stimulate precocious generation of NSCs by inducing Sox9 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
292
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(313 citation statements)
references
References 50 publications
20
292
1
Order By: Relevance
“…Expression studies have shown that SOX9 is expressed by neuroepithelial cells in the ventricular zone of the developing spinal cord, by oligodendrocytes and by astrocytes but not by neurons (Stolt et al, 2003). Knocking out Sox9 in the developing mouse spinal cord results in perinatal lethality, decreased numbers of oligodendrocyte progenitors and astrocytes and an increased number of motor neurons (Stolt et al, 2003) and neuroblasts (Scott et al, 2010). MicroRNA studies also suggest that SOX9 is gliogenic, promoting neural stem cells to adopt an astrocyte or oligodendrocyte fate (Cheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Expression studies have shown that SOX9 is expressed by neuroepithelial cells in the ventricular zone of the developing spinal cord, by oligodendrocytes and by astrocytes but not by neurons (Stolt et al, 2003). Knocking out Sox9 in the developing mouse spinal cord results in perinatal lethality, decreased numbers of oligodendrocyte progenitors and astrocytes and an increased number of motor neurons (Stolt et al, 2003) and neuroblasts (Scott et al, 2010). MicroRNA studies also suggest that SOX9 is gliogenic, promoting neural stem cells to adopt an astrocyte or oligodendrocyte fate (Cheng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 5AdC-induced SKNAS sphere culture grown in the sphere-forming condition without 5AdC for 1.5 y (day 592) expressed higher levels of SOX2, CD133, and neural crest stem cell markers (p75 NTR , SOX9, SOX10, SLUG, Musashi-1) compared with the non-drug-treated sphere culture and the monolayer counterpart (Fig. 1C), suggesting that these SKNAS spheres express a phenotype more similar to neural crest stem cells (14)(15)(16)(17)(18). Immunocytochemical assay further showed that the 5AdC-induced SKNAS spheres at Fig.…”
Section: Short-term Treatments With Epigenetic Modifiers Enhance the mentioning
confidence: 97%
“…To address whether motif enrichment predicts TF binding and examine the function of enhancer-bound TFs, we chose to focus on the NFI family, since the NFI motif was the most prevalent in quiescent NSC enhancers, and these factors were not previously known to regulate NSC biology, whereas the functions of Sox and bHLH factors have already been extensively studied in these cells (Bylund et al 2003;Ligon et al 2007;Scott et al 2010;Castro et al 2011). Our RNA-seq, immunocytochemistry, and Western blot data showed that the four members of the NFI family (NFIA, NFIB, NFIC, and NFIX) are expressed in both proliferating and quiescent NSCs, but NFIX is up-regulated when NS cells become quiescent (the nuclear protein ratio in quiescent cells/proliferating cells is 226%), while NFIA, NFIB, and NFIC are down-regulated or unchanged (64%, 51%, and 87%, respectively) ( Fig.…”
Section: Widespread Binding Of Nfi Tfs To Quiescent Ns Cell Enhancersmentioning
confidence: 99%